Clinical Characteristics, Surgical Management and Adjuvant Therapy of Patients with Uterine Leiomyosarcoma: 27 Years of Experience - Rothmund, R.; Huebner, M.; Joachim, C.; Hartkopf, A.; Fehm, T.; Bamberg, M.; Wallwiener, M.; Brucker, S.; Taran, F. A. (Geburtshilfe und Frauenheilkunde, 2011)
Purpose: To review a single-center experience over a 27-year period in the management of uterine leiomyosarcoma (LMS) for insight into surgical practice, adjuvant therapy and clinical outcome. Material and Methods: This was a retrospective study of women with histologically proven uterine LMS who were treated at the Department of Obstetrics and Gynecology, University of Tuebingen, Germany, between 1983 and 2010. Inpatient and ambulatory records were reviewed; follow-up and survival data were ascertained. Results: The study sample comprised 32 patients with uterine LMS. Primary surgical treatment consisted of total abdominal hysterectomy in 28 patients (88 %) and laparoscopic total hysterectomy in 4 patients (12 %). Lymph nodes were dissected and evaluated in 17 women (53 %); positive lymph nodes were present in 1 patient (6 %). A total of 17 patients (53 %) received adjuvant therapy. Median follow-up for disease-free survival (DFS) was 35.6 months and median DFS was 27.0 months for all patients. The median follow-up for overall survival (OS) was 51.3 months and the median OS was 28.0 months for our study group. The 5-year survival rate was 30 %. There was no significant difference in DFS (p = 0.76) and OS (p = 0.51) between patients who received adjuvant therapy and those who did not. Conclusion: Uterine LMS are rare and aggressive uterine neoplasms with high recurrence rates and metastatic potential. Surgery consisting of total hysterectomy with or without bilateral salpingo-oophorectomy is the most important treatment-element in patients with uterine LMS. Lymphadenectomy should be reserved for patients with clinically suspicious nodes.
Keywords: leiomyosarcoma; uterine neoplasms; lymphadenectomy; adjuvant therapy